Utility of Time-Variant Multiphase CTA Color Maps in Outcome Prediction for Acute Ischemic Stroke Due to Anterior Circulation Large Vessel Occlusion - Ospel, Johanna M; Cimflova, Petra; Volny, Ondrej; Qiu, Wu; Hafeez, Moiz; Mayank, Arnuv; Najm, Mohamed; Chung, Kevin; Kashani, Nima; Almekhlafi, Mohammed A; Menon, Bijoy K; Goyal, Mayank (Clinical neuroradiology, 2021)
BACKGROUND: Multiphase CTA (mCTA) is an established tool for endovascular treatment decision-making and outcome prediction in acute ischemic stroke, but its interpretation requires some degree of experience. We aimed to determine whether mCTA-based prediction of clinical outcome and final infarct volume can be improved by assessing collateral status on time-variant mCTA color maps rather than using a conventional mCTA display format. METHODS: Patients from the PRove-IT cohort study with anterior circulation large vessel occlusion were included in this study. Collateral status was assessed with a three-point scale using the conventional display format. Collateral extent and filling dynamics were then graded on a three-point scale using time-variant mCTA color-maps (FastStroke, GE Healthcare, Milwaukee, WI, USA). Multivariable logistic regression was performed to determine the association of conventional collateral score, color-coded collateral extent and color-coded collateral filling dynamics with good clinical outcome and final infarct volume (volume below vs. above median infarct volume in the study sample). RESULTS: A total of 285 patients were included in the analysis and 53% (152/285) of the patients achieved a good outcome. Median infarct volume on follow-up was 12.6 ml. Color-coded collateral extent was significantly associated with good outcome (adjusted odds ratio [adjOR] 0.53, 95% confidence interval [CI]:0.36-0.77) while color-coded collateral filling dynamics (adjOR 1.30 [95%CI:0.88-1.95]) and conventional collateral scoring (adjOR 0.72 [95%C:0.48-1.08]) were not. Both color-coded collateral extent (adjOR 2.67 [95%CI:1.80-4.00]) and conventional collateral scoring (adjOR 1.84 [95%CI:1.21-2.79]) were significantly associated with follow-up infarct volume, while color-coded collateral filling dynamics were not (adjOR 1.21 [95%CI:0.83-1.78]). CONCLUSION: In this study, collateral extent assessment on time-variant mCTA maps improved prediction of good outcome and has similar value in predicting follow-up infarct volume compared to conventional mCTA collateral grading.
Keywords: ischemie mozku; Brain Ischemia; Humans; Stroke; kohortové studie; lidé; Computed Tomography Angiography; Cerebral Angiography; Collaterals; Cohort Studies; Ischemic Stroke; cévní mozková příhoda; mozková angiografie; Retrospective Studies; kolaterální oběh; ischemická cévní mozková příhoda; retrospektivní studie; Large vessel occlusion; Collateral Circulation; Ischemic stroke; CT angiografie